The Influence of Employer Branding and the Use of Social Media on Gen Z's Intention to Apply Works through Corporate Reputation as Mediation - siti zahra zahira; Juniwati, Juniwati; Fahruna, Yulyanti; Fauzan, Rizky; Syahbandi, Syahbandi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
GeniZiisiknownitoihaveitheiabilityitoibeiskillediiniusingitheiinternet,inamelyisocialimedia,iespeciallyiiniseekingiinformationiaboutitheireputationiofianiorganizationioricompany.iThisiisianiimportantiinvestmentiforicompaniesitoigetipotentialiemployees.iToiattractiGeniZitoiapplyiforijobs,icompaniesimustihaveiemployeribranding,iaisocialimediaipresenceiandiaigoodireputation.iThisistudyiaimsitoievaluateihowiemployeribrandingiandisocialimediaiuseiaffectitheileveliofiintentionitoiapplyiforiaijob,itakingiintoiaccountitheiroleioficorporateireputationiasianiintermediary.iThisistudyiusesiaiquantitativeiapproachiwithidataicollectionithroughiaiquestionnaireisurveyidistributeditoi200ialumniiofiTanjungpuraiUniversityistudents.iTheipurposiveisamplingitechniqueiwasiuseditoiselectirespondentsiwhoihadicertainicriteria,inamelyigeniziagedi17-27iyearsiandialumniiofiTanjungpuraiUniversity.iTheidataiwasianalyzediusingipathianalysisitechniquesiandiIBMiSPSSiStatisticisoftware.iThisiresearchiisiexpecteditoiprovideiinsightiforihumaniresourceimanagersiandipractitionersiinidesigningistrategiesitoiincreaseitheiworkiinterestiofiGeniZ.iTheiresultsiofithisistudyishowithatiemployeribrandingianditheiuseiofisocialimediaihaveiaipositiveiandisignificantiinfluenceionitheirateiofiintentionitoiapplyiforiaijobiiniGeniZimediatedibyitheiCompany'siimage.